2015
DOI: 10.4103/0019-5049.151367
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microcuff®endotracheal tubes in paediatric laparoscopic surgeries

Abstract: Background and Aims:Traditionally, uncuffed endotracheal tubes have been used in children. Cuffed tubes may be useful in special situations like laparoscopy. Microcuff® endotracheal tube is a specifically designed cuffed endotracheal tube for the paediatric airway. We studied the appropriateness of Microcuff® tube size selection, efficacy of ventilation, and complications, in children undergoing laparoscopy.Methods:In a prospective, observational study, 100 children undergoing elective laparoscopy were intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Tube exchange was required in the remaining 12% of the patients. It has been found that the tube exchange rate was either low (2.1%) or none with the use of this age-related formula for tube size selection from the findings made by Weis et al [1] and Mhamane et al [13] The difference in this finding noted in our study can be due to the difference in patient characteristics. The four patients in whom the inappropriateness of tube selection noted was found to have height and weight below the 50 th percentile of height and weight for age.…”
Section: Discussioncontrasting
confidence: 59%
“…Tube exchange was required in the remaining 12% of the patients. It has been found that the tube exchange rate was either low (2.1%) or none with the use of this age-related formula for tube size selection from the findings made by Weis et al [1] and Mhamane et al [13] The difference in this finding noted in our study can be due to the difference in patient characteristics. The four patients in whom the inappropriateness of tube selection noted was found to have height and weight below the 50 th percentile of height and weight for age.…”
Section: Discussioncontrasting
confidence: 59%
“…Mahmoodpoor et al 7 evaluated comparison of prophylactic effects of polyurethane cylindrical or tapered cuff and PVC cuff ETTs on ventilator associated pneumonia and maintained mean cuff pressure in PVC ETT was 24.20 ± 0.47 mmHg, in polyurethane taperguard ETT was 24.10 ± 0.49 mmHg and 24.07 ± 0.48 mmHg was for polyurethane sealguard ETT ( P > 0.05). Mhamane et al 11 evaluated use of microcuff ETTs in pediatric laparoscopic surgeries. They observed mean sealing pressure was 11.72 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, the need for continuous pressure monitoring adds more obstacles to the microcuff ETT usage. 18…”
Section: Discussionmentioning
confidence: 99%